Schaumsklerosierung: Anwendung und Indikation in der Dermatologie und Phlebologie - Heck, Markus; Faulhaber, Jörg; Schneider, Stefan W. (Der Hautarzt, 2012)
Foam sclerotherapy is a minimally invasive, effective technique for the treatment of varicoses up though venous malformations. This efficient therapy can be easily integrated in daily clinical practice and shows only minor side effects. It provides an alternative to invasive therapies like vein stripping, endovenous laser therapy or endovenous radiofrequency ablation, but without the need for anesthesia. The treatment can be performed in an outpatient setting and the patient is able to return quickly to everyday life.
Gesehen am 22.10.2018